Volume Unit in the Period of The Prophet Muhammad Sallallahu Alayhi Wa Sallam: An Integrated Study of Mathematics and Islamic Histories within the Contemporary Context - Awi Dassa; Syahrullah Asyari; Ikhbariaty Kautsar Qadry (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2019)
This article aims at presenting one of the mathematics topics in Islamic history, namely volume unit which had been used by Arabians in the medieval age, especially by the Prophet Muhammad Sallallahu Alayhi Wa Sallam. It is something rarely revealed by, or even never be found in the literature of mathematics history by Western mathematics historians. The study results show that in the period of Muhammad Sallallahu Alayhi Wa Sallam, Arabians used Qullah unit in determining the volume of an object, where 1 Qullah is about 96 liters so that 2 Qullahs will be about 192 liters. It is in line with the result of the computation mathematically based upon the explanation of scholars in contemporary Islamic Jurisprudence